Legal disputes over maritime piracy - United Nations Interregional Crime; Justice Research Institute (Freedom from Fear, 2009)
Somalia is not party to any of the relevant international treaties and does not have any modern domestic legislation directly applicable to piracy or environmental protection. However, the countries currently providing naval forces to combat piracy at sea off Somalia are parties to one or more of the relevant treaties. In addition, neighboring countries such as Kenya, Djibouti, Yemen and Tanzania are also parties to some or all of these treaties, and these countries have enacted the legislation necessary to implement one or more of the treaties.